Molecular structure, spectroscopic properties and quantum chemical calculations of 8-t-buthyl-4-methyl-2H-chromen-2-one - Koparir, Pelin; Sarac, Kamiran; Orek, Cahit; Koparir, Metin (Elsevier, 2016)
This study acquaints the 8-t-buthyl-4-methyl-2H-chromen 2-one (II) of by quantum chemical calculations and spectral ways. The molecular geometry, vibrational frequencies and gauge including atomic orbital (GIAO) H-1 and C-13 NMR chemical shift values of II in the ground state have been calculated utilizing the density functional method (B3LYP) with the 6-31G(d) basis set. The theoretical vibrational frequencies and chemical shift values display well agreement with experimental values. On the other hand, DFT calculations of molecular electrostatic potentials and frontier molecular orbitals of II were implemented at the B3LYP/6-31G(d) level of theory. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Coumarins 8-t-Buthyl-4-methyl-2H-chromen-2-one; DFT; NMR; FT-IR spectra